2022
DOI: 10.5937/ejae19-35881
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit in the COVID-19 environment: Key aspects and perspectives of remote auditing

Maja Kljajić,
Vule Mizdraković,
Blaženka Hadrović-Zekić

Abstract: It was very difficult to predict the global pandemic caused by the new coronavirus COVID-19 disease that spread around the world. There is no doubt that the pandemic will have a serious impact on worldwide economy because besides causing a health crisis, the pandemic threatens to generate an economic and financial crisis. Therefore, the management of service providing entities were faced with a challenge of finding a model to perform their business activities and take care of the employees' health at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Besides, the interest in WFH is not only limited to external auditors, but also internal auditors. Based on a study of Serbian certified internal auditors, it was found that the audit quality level as well as the audit client management trust level either increased or remained the same when audits were performed via WFH, especially during the pandemic (Kljajic, Mizdrakovic & Hadrovic-Zekic, 2022).…”
Section: Readiness To Wfhmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the interest in WFH is not only limited to external auditors, but also internal auditors. Based on a study of Serbian certified internal auditors, it was found that the audit quality level as well as the audit client management trust level either increased or remained the same when audits were performed via WFH, especially during the pandemic (Kljajic, Mizdrakovic & Hadrovic-Zekic, 2022).…”
Section: Readiness To Wfhmentioning
confidence: 99%
“…To measure the readiness of Malaysian auditors to WFH, several additional items were tested under individual and firm readiness using a similar five-point Likert-scale (Baker, Avery & Crawford, 2007;Kljajic, Mizdrakovic, & Hadrovic-Zekic, 2022;Ranganathan, 2018;Weeks, 2004). Overall, 29 items comprising the impact of Covid-19 on the execution of audits and the readiness of Malaysian auditors to WFH were used in the study, as listed in Table 2.…”
Section: Instrumentation and Analytical Proceduresmentioning
confidence: 99%
“…[2] Remote audit yang dilakukan memiliki banyak keuntungan daripada kerugiannya pada saat pandemi (Kljajić et al, 2022).…”
Section: Hasil Penelitian Sebelumnyaunclassified